Pentingnya Kepatuhan Keamanan Informasi Dalam Mengurangi Risiko Data Breach - Ripa Sabila Usni Sitompul; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out how vital information security compliance is in reducing the risk of Data Breach. The method used in this research is Library Research (Library) which is the method used in this writing, and in its use, this method uses books, and journals both in written form and online. Based on the results obtained from this research, it can be concluded that a Data Breach is an incident where sensitive data or important information becomes vulnerable or is accessed by unauthorized parties. To prevent a Data Breach, organizations need to take various security measures, policies, and practices, such as encryption, access management, physical security, network security, security training and awareness, security policies, and monitoring and auditing. Sensitive data protection helps maintain the confidentiality, integrity, and availability of data and protects the reputation and trust of customers and business partners. By implementing good sensitive data protection, organizations can reduce the risk of data breaches which can be financially detrimental and damage the company's image.